2022
DOI: 10.1016/j.jaci.2021.12.777
|View full text |Cite
|
Sign up to set email alerts
|

Helminth infections and allergic diseases: Systematic review and meta-analysis of the global literature

Abstract: Background: There is considerable research interest in the role of helminth infections in the development of allergic diseases. However, findings from previous studies are mixed. Existing systematic reviews of these studies are outdated. We performed a systematic review of the global literature on the association between helminth infections and development and clinical outcomes of allergic diseases. Methods: We searched Cochrane Library, MEDLINE, EMBASE, ISI Web of Science, PubMed, Global Index Medicus, Scielo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 97 publications
1
9
0
Order By: Relevance
“…Thus, chronic helminth infections may protect from allergic diseases including asthma [ 51 54 ]. In such a scenario our results with respect to wheeze and A. lumbricoides could be seen as counter-intuitive, but they are, nevertheless, entirely in accordance with the conclusions drawn by reviews of recent studies on the topic of associations between STH and symptoms of asthma, including those of a systematic nature with meta-analyses [ 26 , 55 , 56 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Thus, chronic helminth infections may protect from allergic diseases including asthma [ 51 54 ]. In such a scenario our results with respect to wheeze and A. lumbricoides could be seen as counter-intuitive, but they are, nevertheless, entirely in accordance with the conclusions drawn by reviews of recent studies on the topic of associations between STH and symptoms of asthma, including those of a systematic nature with meta-analyses [ 26 , 55 , 56 ].…”
Section: Discussionsupporting
confidence: 89%
“…The evidence linking helminth infections with allergic diseases is controversial. While several studies have shown inverse associations between helminths and allergy [22][23][24][25], a recent review suggested that Ascaris lumbricoides infections may increase the risk of bronchial hyperreactivity in participants and of atopy in adults [26]. Notably, helminth elimination as a public health problem is integrated into the WHO roadmap for Neglected Tropical Diseases 2021-2030 [27].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review and meta‐analysis of epidemiological studies reported that helminth infections may increase the risk of bronchial hyperreactivity in children and atopy in adults 35 . A murine study demonstrated that infection with helminth parasites may modulate the host immune response to allergic asthma directly or by altering the host gut microbiota 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Schistosomiasis has been regarded as a protective factor against atopy and asthma [41,42], depending on the parasite burden and chronicity of the infection [43]. However, some studies have shown that anti-schistosome IgE is positively associated with specific sensitization (e.g., to mites or cockroaches) and allergic diseases [3,44,45]. In addition, in vivo models have used sensitization and challenge with Schistosoma eggs to induce type-2 inflammation [46], suggesting the presence of components with allergenic activity.…”
Section: Schistosoma Sppmentioning
confidence: 99%